2019
DOI: 10.32479/irmm.7714
|View full text |Cite
|
Sign up to set email alerts
|

Social Media as a Strategic Marketing Communication Tool in Palestinian Mobile Telecom Companies - Business to Customers Relationship Perspective

Abstract: The aim of the research is to identifying the role of social media in building customer relationships; the study also aims at using social media as a strategic marketing tool for telecom companies. The researcher used Jawwal as a case study in the aspect of: (brand awareness, knowledge of services and products, and intention to purchase). Through a quantitative approach by designing a survey questionnaire as a tool of collecting data. The sample included (432) of Jawwal Customer's Mobile Telecom Company in Pal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…(Bharadwaj & Shipley, 2020;Liang, 2021;Lyu, 2021). Several studies have found that marketing communication will create quality relationships between companies and their customers (Diebes & Iriqat, 2019;Ipang, et al, 2021;Özsaçmacı & Dursun, 2020). In this study, researchers expect communication effectiveness to influence customer engagement.…”
Section: Communication Effectivenessmentioning
confidence: 81%
“…(Bharadwaj & Shipley, 2020;Liang, 2021;Lyu, 2021). Several studies have found that marketing communication will create quality relationships between companies and their customers (Diebes & Iriqat, 2019;Ipang, et al, 2021;Özsaçmacı & Dursun, 2020). In this study, researchers expect communication effectiveness to influence customer engagement.…”
Section: Communication Effectivenessmentioning
confidence: 81%
“…This will assist you keep the clients you now have while also attracting new ones. Because of recent improvements in customer relationship management (CRM), businesses are now able to better understand the requirements and preferences of the clients they serve [15]. This transformation, which is made possible by a knowledge of the firm's existing clientele, is enabled by the CRM strategy that is used by the company to help customers in the process of being transformed into resources [16].…”
Section: Advancement Of Customer Relationship Managementmentioning
confidence: 99%
“…Organisations that implement social media marketing strategies after taking customer concerns and ideas into consideration may emerge as winning organisations (Diebes & Iriqat, 2019). The theoretical framework of the present study is based on a model for a customer engagement cycle introduced by Sashi (2012), which encompasses seven stages, namely, connection, interaction, satisfaction, retention, commitment, advocacy, and engagement.…”
Section: Smes' Awareness Of Customer Perspectives On Social Mediamentioning
confidence: 99%
“…They assess how people spend their time online and create entertaining content to boost brand exposure (Lindsey-Mullikin & Borin, 2017). Therefore, there is a timely need for organisations to understand how customers perceive and react to the shared content on social media, if they are to boost their organisational growth (Diebes & Iriqat, 2019). Hence, the following hypothesis is formulated: H2: SMEs' awareness of customer perspectives towards social media has an impact on business performance…”
Section: Smes' Awareness Of Customer Perspectives On Social Mediamentioning
confidence: 99%